A snapshot of nutritional recommendations and management practices adopted by feedlot cattle nutritionists in Brazil in 2023 - Monsalve, Julia Gabrielle; Millen, Danilo Domingues (Frontiers in Veterinary Science, 2025)
IntroductionThis survey was conducted to provide an overview of the nutritional strategies and management practices used by feedlot nutritionists in Brazil.MethodsThe online questionnaire consisted of 100 questions and covered a wide range of topics, including information about nutritionists, ingredients used in finishing diets, feeding strategies, management practices, challenges in applying nutritional recommendations, and animal performance results.ResultsThe 36 participating nutritionists were responsible for 6,082,698.52 animals, representing 79.8% of the cattle from feedlots slaughtered in 2023. Corn remains the preferred grain choice among nutritionists, with 91.7% of the responses. Regarding the grain processing used, the high-moisture re-hydrating and storage was chosen by 34.3% of participants, overcoming other methods of grain processing, such as grinding, which reflects the continuous search for starch optimization in the Brazilian feedlots. Coproducts have been widely used in finishing diets in Brazilian feedlots, with 92.7% of nutritionists’ clients reporting its use, highlighting a focus on sustainable and economically viable practices. In this context, dried distillers’ grains have established a strong position in the Brazilian market as an important coproduct source to meet protein demands, being chosen as the primary protein source for the first time in feedlot history in Brazil. This study also emphasizes the widespread use of technologies at the operational level, with 80.8% of feedlots reporting the use of truck-mounted mixers and 81.4% adopting feed deliveries by pen. These practices have enabled feedlot nutritionists to increase the energy level of finishing diets, resulting in higher use of peNDF (85.3%) and more accurate monitoring of the amount of fiber available for rumination. Additionally, animal welfare practices have been implemented, such as shading in pens (18.8%) and the use of sprinklers (53.1%).ConclusionThe data collected point to a notable change in the diets and management practices of Brazilian feedlots. This evolution reflects an adaptation to the needs of the sector, as well as a growing commitment to efficiency and sustainability. These trends point to a promising future for feedlots in Brazil and highlight the continued need for research and innovation to drive feedlot operations to advanced practices.